THE ROLE OF THE SPIRITUAL FACTOR IN ENSURING THE INFORMATION AND PSYCHOLOGICAL SECURITY OF THE ARMED FORCES - Gafurov Alexander Valerevich (Journals Park Publishing, 2024)
In the modern era, when information warfare and psychological threats are escalating, ensuring the security of the armed forces is beyond physical measures. This scientific article explores the decisive role of the spiritual factor in ensuring the information and psychological security of the Armed Forces. It explores ethical principles, values, and thought that contribute to the resilience and effectiveness of military personnel in information manipulation, psychological operations, and moral dilemmas. Emphasizing the interrelationship between spiritual power, Information Security and psychological well-being, this article emphasizes the importance of forming a solid moral foundation within the Armed Forces.